AVALIAÇÃO DO PROGRAMA DE MONITORAMENTO DE AVES MIGRATÓRIAS DURANTE A IMPLANTAÇÃO DE PÍER EM SÃO LUÍS - MA - Pereira, Daniel Rocha (2014)
Assessment of compliance of the Program Monitoring Migratory Birds (PMMB) during deployment pier in San Luis - MA, through documents obtained from the entrepreneur and the environmental agency. It was shown in this study that several PMMB guidelines were not followed and the results showed different patterns of the studies of other authors for the same region. Therefore, the PMMB was not completed as proposed and the results of monitoring may have been committed in this sense is not possible to define the dynamics of interference in birds studied by the project.